Orang Punan Batu Benau Sajau: Kesinambungan Hunter-Gatherer dan Warisan Budaya Karst di Kalimantan Utara - Prasetijo, Adi (JANUS, 2025)
The Benau Karst Hills in Bulungan Regency, North Kalimantan, form an ecological and cultural space that is central to the lives of the Punan Batu Benau Sajau people. For them, karst caves serve as temporary dwellings, storage spaces for forest products, and sites for cosmological rituals. This study adopts a landscape archaeological perspective to understand the connection between the contemporary practices of the Punan Batu, a hunter-gatherer society, and archaeological evidence of cave dwellings in Kalimantan. It was conducted through brief ethnographic observations (2025), a review of archaeological literature, and integration with genetic findings that confirm the continuity of Punan Batu culture. The results suggest that the Benau karst landscape can be perceived as a cultural landscape, where the subsistence practices, mobility, and cosmology of the local community reflect continuity with prehistoric cave-dwelling practices. This study highlights that preserving customary forests is not only a legal and ecological concern but also vital for maintaining the living archaeological heritage of Southeast Asia. === Bukit Karst Benau di Kabupaten Bulungan, Kalimantan Utara, merupakan ruang ekologis dan budaya yang menjadi pusat kehidupan masyarakat Punan Batu Benau Sajau. Bagi mereka, gua-gua karst berfungsi sebagai tempat tinggal sementara, ruang penyimpanan hasil hutan, hingga lokasi ritual kosmologis. Studi ini berangkat dari perspektif arkeologi lanskap untuk memahami keterhubungan antara praktik kontemporer Punan Batu sebagai masyarakat berburu-meramu dengan bukti arkeologis hunian gua di Kalimantan. Kajian ini dilakukan melalui observasi etnografi singkat (2025), studi literatur arkeologi, serta integrasi dengan temuan genetika yang menegaskan kesinambungan budaya Punan Batu. Hasil kajian ini menunjukkan bahwa lanskap karst Benau dapat dipandang sebagai lanskap budaya, ketika praktik subsistensi, mobilitas, dan kosmologi komunitas lokal mencerminkan kesinambungan dengan praktik hunian gua prasejarah. Studi ini menegaskan bahwa pelestarian hutan adat bukan hanya urusan hukum dan ekologi, melainkan juga pelestarian warisan arkeologi hidup yang masih berlangsung di Asia Tenggara.